2012
DOI: 10.1007/s12328-012-0326-1
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatoduodenectomy for circumportal pancreas accompanying the retroportal pancreatic duct: a case report and review of the literature

Abstract: Circumportal pancreas (CP) is an extremely rare pancreatic fusion anomaly which is usually asymptomatic. This report presents the case of a patient with a tumor in the head of a CP and the retroportal accessory pancreatic duct in the pancreatic tissue behind the portal vein. A 53-year-old male was diagnosed with a nonfunctioning neuroendocrine tumor of the pancreas and resection of the tumor was scheduled. The patient was revealed to have CP on preoperative computed tomography and endoscopic retrograde cholang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The second procedure uses the communication between MPD and the accessory pancreatic duct (APD), which courses in the parenchyma opposite to the one containing MPD. Pardiwala and Maker 18 and Shonaka et al 14 and reported successful ligations of the retroportal pancreatic parenchyma and the pancreaticoenteric anastomosis above the PV in cases that showed communication between MPD and APD at the left side to PV. Thus, it is important to note that a surgeon should determine whether APD exists, the location of the APD, and its relation to the MPD when planning pancreatic surgery in a patient with PAP.…”
Section: Discussionmentioning
confidence: 99%
“…The second procedure uses the communication between MPD and the accessory pancreatic duct (APD), which courses in the parenchyma opposite to the one containing MPD. Pardiwala and Maker 18 and Shonaka et al 14 and reported successful ligations of the retroportal pancreatic parenchyma and the pancreaticoenteric anastomosis above the PV in cases that showed communication between MPD and APD at the left side to PV. Thus, it is important to note that a surgeon should determine whether APD exists, the location of the APD, and its relation to the MPD when planning pancreatic surgery in a patient with PAP.…”
Section: Discussionmentioning
confidence: 99%